2001
DOI: 10.1023/a:1013349512683
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Individual differences in inspection time explain about 20% of IQ test variance. To determine whether the association between inspection time and IQ is mediated by common genes or by a common environmental factor, inspection time and IQ were assessed in an extended twin design. Data from 688 participants from 271 families were collected as part of a large ongoing project on the genetics of adult brain function and cognition. The sample consisted of a young adult cohort (mean age 26.2 years) and an older adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
21
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…The subjects for whom MRI scans were available partly overlapped with a sample of extended twin families from a large study on cognition 4 . In the latter study, we found a heritability of g of 0.86, which is consistent with previous reports 5 .…”
mentioning
confidence: 99%
“…The subjects for whom MRI scans were available partly overlapped with a sample of extended twin families from a large study on cognition 4 . In the latter study, we found a heritability of g of 0.86, which is consistent with previous reports 5 .…”
mentioning
confidence: 99%
“…The importance of studying individual difference in IPS was emphasized by Wilhelm Wundt, Sir Francis Galton, and James Mckenn Cattell during the late 1800s and early 1900s. However, due to general decline in IPS research up until late nineteenth century only during the past decades IPS changes in clinical populations began to be understood (O'Brien & Tulsky, 2008).…”
mentioning
confidence: 99%
“…General slowing of information processing is also related to psychia tric disorders, such as depression (Reppermund et al, 2007;Tsourtos, Thompson, & Stough, 2002), schizophrenia (Brebion et al, 2015;Cella & Wykes, 2013), schizoaffective disorder (Fryar-Williams & Strobel, 2015;Simonsen et al, 2011) and others. These relatively consistent findings of IPS group differences between healthy controls and mental illness could contribute to more general investigations of mechanisms underlying individual differences in IPS.…”
mentioning
confidence: 99%
See 2 more Smart Citations